Magnetic order and superconductivity observed in bundles of double-wall carbon nanotubes. (July 2015) - Barzola-Quiquia, J.; Esquinazi, P.; Lindel, M.; Spemann, D.; Muallem, M.; Nessim, G.D.
Abstract: The magnetotransport properties were studied in hundreds of micrometer length double-wall carbon nanotubes (DWCNT) bundles. Above 15 K the resistance shows an ohmic behavior and its temperature dependence is well described using the variable-range hopping for one-dimensional system. The magnetoresistance is negative and can be explained using an empirical model based on spin-scattering processes indicating the existence of magnetic order up to room temperature. At temperatures between 2 and 15 K the resistance is non-ohmic and the current–voltage characteristics reveal the appearance of a potential, which can be well described by a fluctuation-induced tunneling conduction model. In this low temperature range and at low enough input current, a positive magnetoresistance appears – in addition to the negative one – with an extraordinary hysteresis in field and vanishes at T  ∼ 15 K, suggesting the existence of a superconducting state. Magnetization results partially support the existence of both phenomena in the DWCNT bundles.